2021
DOI: 10.1089/vio.2020.0069
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and the Increased Violence Against Women: Understanding Domestic Violence During a Pandemic

Abstract: Globally, during the COVID-19 pandemic lockdown, reports of domestic abuse have increased. Using scientific and news reports about violence against women during COVID-19 and the changes it implicated in society, this article speculates how different factors contribute to violence against women worldwide, with some focus on Lebanon. Violence types addressed in this study will be domestic violence and intimate partner violence. To understand the link between violence against women and the multidimensional interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 25 publications
0
39
0
2
Order By: Relevance
“…Advocates also reported concerns about increased complexities and challenges in assisting victims/survivors amidst COVID‐19 (Foster, 2020 ). By the completion of our survey, there was a growing body of international evidence that there was an increase in DFV during this period (Boserup et al, 2020 ; Bouillon‐Minois et al, 2020 ; Bradbury‐Jones & Isham, 2020 ; Bradley et al, 2020 ; Chandan et al, 2020 ; Froimson et al, 2020 ; Kofman & Garfin, 2020 ; Mazza et al, 2020 , Peterman et al, 2020 ; Usta et al, 2021 ). In the absence of reliable data, most of these studies quote increases in calls to domestic violence helplines of between 15–30% as evidence of an increase in prevalence.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Advocates also reported concerns about increased complexities and challenges in assisting victims/survivors amidst COVID‐19 (Foster, 2020 ). By the completion of our survey, there was a growing body of international evidence that there was an increase in DFV during this period (Boserup et al, 2020 ; Bouillon‐Minois et al, 2020 ; Bradbury‐Jones & Isham, 2020 ; Bradley et al, 2020 ; Chandan et al, 2020 ; Froimson et al, 2020 ; Kofman & Garfin, 2020 ; Mazza et al, 2020 , Peterman et al, 2020 ; Usta et al, 2021 ). In the absence of reliable data, most of these studies quote increases in calls to domestic violence helplines of between 15–30% as evidence of an increase in prevalence.…”
Section: Discussionmentioning
confidence: 95%
“…A meta‐search of international available evidence concluded that “The lockdown exacerbated several factors that affect violence against women”. The drivers of DFV are complex but include increased household tensions, affected gender roles, decreased independence, decreased access to supportive services, decreased stress‐relieving activities and increased economic burden (Usta et al, 2021 :5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, our nationwide survey contributes to the growing evidence globally (e.g., see Peterson, et al 2020; Piquero et al 2020;Polischuk and Fay 2020;True et al 2020;Usta, Murr and El-Jarrah 2021) about the effect of COVID-19 on increasing the complexities of clients' experiences, who were accessing domestic violence and related support services during the onset of the pandemic. Our Australian study reveals an alarming picture with an overwhelming 86.5% (n = 313) of service providers reporting the pandemic had increased the complexity of their clients' needs.…”
Section: Conclusion and Recommendationsmentioning
confidence: 90%
“…It was found that one of the main reasons that domestic violence increases during a virus outbreak is the breakdown and reformation of laws [19], which includes the implementation of lockdowns. Such periods of forced proximity between partners increases the time spent together, and impedes victims of domestic violence from "escaping" their home (such as going to work or to social events) [46,47]. Additionally, due to the fact that social services and police have different emergencies and priorities during a pandemic, victims of domestic abuse may not be as well supported as they were before the pandemic.…”
Section: Domestic Violence Against Women and Covid-19mentioning
confidence: 99%